2013
DOI: 10.1016/j.virol.2012.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Simian–Human immunodeficiency viruses expressing chimeric subtype B/C Vpu proteins demonstrate the importance of the amino terminal and transmembrane domains in the rate of CD4+ T cell loss in macaques

Abstract: Previously, we reported that simian-human immunodeficiency viruses expressing either the lab adapted subtype B (SHIVKU-1bMC33) or subtype C (SHIVSCVpu) Vpu proteins of human immunodeficiency virus type 1 (HIV-1) had different rates of CD4+ T cell loss following inoculation into macaques. In this study, we have generated SHIVs that express either the subtype B or subtype C N-terminal (NTD) and transmembrane (TMD) domains and the opposing cytoplasmic domain (SHIVVpuBC, SHIVVpuCB). In culture systems, the SHIVVpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…There is accumulating evidence that HIV-1 subtype B and C Vpu proteins differ in their functional properties. Whereas B Vpus degrade CD4 efficiently and interfere with tetherin expression and virus particle release, some studies have shown that C Vpus are less potent in these functions although the number of Vpu proteins analyzed was limited 32 40 41 . In this study, comparing 12 subtype B and 9 subtype C Vpu proteins, we found that subtype C Vpus were significantly weaker CD1d antagonists than their subtype B counterparts ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that HIV-1 subtype B and C Vpu proteins differ in their functional properties. Whereas B Vpus degrade CD4 efficiently and interfere with tetherin expression and virus particle release, some studies have shown that C Vpus are less potent in these functions although the number of Vpu proteins analyzed was limited 32 40 41 . In this study, comparing 12 subtype B and 9 subtype C Vpu proteins, we found that subtype C Vpus were significantly weaker CD1d antagonists than their subtype B counterparts ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was in preparation a study using SHIVs expressing chimeric Vpu molecules composed of either a Vpu B N -terminus (luminal and transmembrane domains) with a Vpu C C -terminus or its reciprocal concluded that the in vivo rate of CD4+ T-cell loss in macaques was dependent on the source of the Vpu N -terminus. The SHIV expressing the chimeric Vpu with the N -terminus derived from Vpu B had a more rapid loss of T-cells compared to the chimeric Vpu composed of the Vpu C N -terminus or the parental Vpu C (Ruiz et al, 2012). A mechanism for the increased pathogenesis associated with the N -terminus from Vpu B was not readily apparent.…”
Section: Discussionmentioning
confidence: 97%
“…In our experimental design, recombination between the Env or EnvEC backbone and the Env or EnvEC amplicon occurs within Vpu, although it is not known where the breakpoint occurs. Vpu is a frequent breakpoint for inter-subtype recombination in vivo [ 122 ] and may impact its efficiency in down modulating BST-2 [ 122 , 123 ] and viruses with recombinant BC [ 123 ] and BF [ 122 ] Vpu are moderately more efficient than subtype B or CB recombinant Vpu in down-modulating BST-2. In our study, viral release tended to be higher for viruses with subtype C gp41CT than for their isogenic counterpart with the gp41CT of NL4.3 ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%